Purification and Physicochemical Characterization of a Novel Thermostable Xylanase Secreted by the Fungus Myceliophthora heterothallica F.2.1.4 - de Oliveira Simões, Lorena Caixeta [UNESP]; da Silva, Ronivaldo Rodrigues [UNESP]; de Oliveira Nascimento, Carlos Eduardo [UNESP]; Boscolo, Maurício [UNESP]; Gomes, Eleni [UNESP]; da Silva, Roberto [UNESP] (Springer Nature, 2019)
Xylanases are enzymes that act in the depolymerization of xylan and that can be used in the food industry, the paper industry, and for bioenergy, among other uses. In this context, particular emphasis is devoted to xylooligosaccharides (XOS) that act as prebiotics, which, under the action of probiotic microorganisms, are capable of positively modifying the intestinal microbiota. In this sense, searching for microbial xylanases stands out as a sustainable strategy for the production of prebiotics. To date, there have been no reports in the literature regarding the purification of native xylanase from Myceliophthora heterothallica F.2.1.4. In this study, a xylanase from this fungus was purified and characterized. The xylanase, with 27 kDa, showed maximum activity at pH 4.5 and 65–70 °C. It maintained more than 80% of its residual activity when exposed to (i) temperatures between 30 and 60 °C for 1 h and (ii) pH 5–10 for 24 h at 4 and 25 °C. These high tolerances to different pH and different temperatures are important properties that add value to this enzyme. The hydrolysates of this enzyme on beechwood xylan, analyzed by HPAE-PAD, were mostly xylobiose (X2) and xylotriose (X3). Hydrolysates were also quantified, being retrieved from 234.2 mg xylooligosaccharides/g of hydrolyzed xylan for 12 h. According to the products obtained from the xylan hydrolysis and its tolerance properties of the enzyme, it has demonstrated potential for application production of xylooligosaccharides for use as prebiotics.
Keywords: Fungal enzyme; Purification; Xylanase; Xylooligosaccharides